A thermodynamic review on solar ponds. (August 2022) - Saxena, Abhishek; Cuce, Erdem; Bandhu Singh, Desh; Mert Cuce, Pinar; Gupta, Parul; Suryavanshi, Ajay; Farrokhi, Mahmoud; El-Sebaii, A.A.
Highlights: Present study focuses on the design methodology and different thermodynamic aspects of a SGSP. Thermodynamic analysis of SGSP for energy, exergy, heat transfer, and shading effect has been discussed. Discussion upon factors affecting the thermal performance of solar ponds is helpful to design them. PCMs and extended fins are found as the two economic solutions to enhance the thermal performance of solar ponds. Abstract: Solar energy is a clean source of renewable energy and people around the world are getting a lot of benefits day by day through the utilization of solar energy technology. Among various solar energy systems, a solar pond is a good energy device which is liable to be the most economic large-scale solar collector. It also has the benefit of being its own thermal energy storage (TES). The present review article focuses on the design methodology and different thermodynamic aspects of a salinity gradient solar pond (SGSP) along with its socio-economic benefits. Thermodynamic analysis of SGSP for energy, exergy, heat transfer, and shading effect has been discussed in much supportive way to the students, research scholars and solar professionals. Technical and general recommendations for future works show the research gap and a great possibility of further research on SGSPs. Overall, through this review study, the one can design a solar pond and carry out a complete thermal analysis of a SGSP with a simple approach.